EFFECT OF DENTAL IMPLANTATION ON QUALITATIVE PROPERTIES OF ORAL FLUID AT EARLY POSTOPERATIVE PERIOD - Ткаченко, П.І.; Гуржій, О.В.; Pankevych А.І.; Bilokon S.О. (World of Medicine and Biology, 2015)
Comparison of the results, obtained in the comparison groups on day 7-8 after surgical intervention showed its prevailing positive dynamics in group II. Supplementary treatment with “Lizomucoid” contributed to oral fluid reproduction, normalization of the pH, the amount of total oxyproline protein and viscosity. However, the level of intermediate mass molecules was 1.3 times higher, indicating about prolongation of the process of wounds healing, and only partial restoration of oral cavity homeostasis after dental implantation during this period of observation. Comparison of the results, obtained in the comparison groups allow to reveal certain benefits in normalization of the level of physical-chemical and biochemical components of mixed saliva in supplementary treatment with “Lizomucoid” mouth rinse in the postoperative period. It contributed to reduction of the number of undesirable effects in the earliest periods of observation by 1.7 times. Perspectives of further research. Patients after dental implantation require not only a short-term drug therapy but also a follow-up rehabilitation measures, list of which does not detailed to date.